2018
DOI: 10.4103/0366-6999.233948
|View full text |Cite
|
Sign up to set email alerts
|

One-year Outcomes in Patients with ST-segment Elevation Myocardial Infarction Caused by Unprotected Left Main Coronary Artery Occlusion Treated by Primary Percutaneous Coronary Intervention

Abstract: Background:Very few data have been reported for ST-segment elevation myocardial infarction (STEMI) caused by unprotected left main coronary artery (ULMCA) occlusion, and very little is known about the results of this subgroup of patients who underwent primary percutaneous coronary intervention (PCI). The aim of this study was to determine the clinical features and outcomes of patients with STEMI who underwent primary PCI for acute ULMCA occlusion.Methods:From January 2000 to February 2014, 372 patients with ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In the present study, a lower incidence was found (0.58%). The discrepancy is related to the fact that previous studies also included subtotal occlusion or critical stenosis of the LMCA, while in this cohort, exclusively, patients with a true ATOLMA referred to primary angioplasty were recruited [ 4 , 6 8 , 10 , 11 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, a lower incidence was found (0.58%). The discrepancy is related to the fact that previous studies also included subtotal occlusion or critical stenosis of the LMCA, while in this cohort, exclusively, patients with a true ATOLMA referred to primary angioplasty were recruited [ 4 , 6 8 , 10 , 11 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…All except one patient presented Killip class III-IV, which reflect the poor clinical status of these patients at presentation. ATOLMA should be suspected in patients with STEMI accompanied by these potentially devastating presentations, and an early invasive strategy should be encouraged in these patients [ 3 , 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ST-elevation myocardial infarction (STEMI) is a leading life-threatening disease worldwide. 1 Although primary percutaneous coronary intervention has been approved as the gold standard therapy for patients with STEMI over the past 20 years, [2][3][4] patients with anterior wall STEMI have a worse prognosis than those with non-anterior wall STEMI. 5 Therefore, developing prognostic markers for patients with STEMI is essential to enable clinicians to develop risk stratifications for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…-One study identified as a cross-sectional study (n=1244) -one as case-control study and -one as a review article [28][29][30].…”
Section: : Total Number Of Articles After Applying Inclusion/exclusimentioning
confidence: 99%